Design of integer‐N PLL frequency synthesiser for E‐band frequency for high phase noise performance in 5G communication systems. Issue 1 (1st January 2020) - Berber, Zakia; Kameche, Samir; Benkhelifa, Elhadj
Abstract : A phase‐locked loop (PLL) frequency synthesiser is designed for 5G E‐band frequency. ADF4155‐PLL chip with an external (loop filter, prescaler, VCO and an external reference oscillator) is simulated using the ADIsimPLL tool. With a third‐order passive filter having 1 MHz loop bandwidth and 45° phase margin, simulation results show that the proposed synthesiser achieves a total phase noise (PN) of −81.50 and −115.7 dBc/Hz at 100 kHz and 10 MHz, respectively, for (71–76 GHz) and −80.39 and −114.7 dBc/Hz at 100 kHz and 10 MHz, respectively, for the highest (81–86 GHz) 5G frequency range even if −160 dBc/Hz VCO noise floor and −170dBc/Hz reference PN floor are integrated in the design. Also, the performance of the system in terms of RMS jitter and reference spurs are verified. The proposed synthesiser for 5G application presents very low reference spurs (−113, −112 dBc) at 50 MHz offset frequency and low RMS jitter (0.39, 0.40 ps) for 70 and 80 GHz frequency band, respectively.